Developing bacteriophage and the predatory bacterium Bdellovibrio bacteriovorus as an alternative therapy for canine otitis externa - Secker, Bailey (2024)
Canine otitis externa (OE) is a complex multifactorial disease and is one of the most common diagnoses for dogs seen in veterinary practices worldwide. Pseudomonas aeruginosa is not a typical constituent of the canine ear microbiota but when present in the canine ear, commonly results in severe chronic infections. Antimicrobial resistance and biofilm formation are common in chronic disease and highlights the need for alternative treatments. In the present study the antimicrobial susceptibility and biofilm forming ability of 253 isolates of P. aeruginosa from canine OE was assessed. This identified that resistance to fluroquinolones was high: namely enrofloxacin (25%), levofloxacin (15%) and ciprofloxacin (13%). Further analysis using genome sequencing implicated mutations in DNA gyrase and topoisomerase genes as the cause of this resistance. Similarly, the majority (82%) of canine P. aeruginosa clinical isolates were found to produce strong levels of biofilm. The use of bacteriophage and the predatory bacterium Bdellovibrio bacteriovorus have both been suggested for their use as novel therapies against a variety of pathogens. Subsequently, bacteriophage were isolated and characterised using the clinical P. aeruginosa isolates. Two lytic bacteriophage, with a wide host range (40%, 34%) in regard to the clinical P. aeruginosa isolates, Pseudomonas phage K9-6 and K9-7, were isolated from wastewater samples. Genotypic analysis suggested these bacteriophage belonged to the genus Pbunavirus. Finally, B. bacteriovorus was shown to prey upon a number of (16%) clinical isolates of P. aeruginosa. These results highlight the potential of bacteriophage and B. bacteriovorus to treat P. aeruginosa infection in cases of canine otitis externa.